Predicting the physiological relevance of in vitro cancer preventive activities of phytochemicals - Howells Lynne M; Moiseeva Elena P; Neal Christopher P; Foreman Bethany E; Andreadi Catherine K; Sun Yi-yang; Hudson E Ann; Manson Margaret M (Acta Pharmacologica Sinica, 2016)
There is growing interest in the ability of phytochemicals to prevent chronic diseases, such as cancer and heart disease. However, some of these agents have poor bioavailability and many of the in-depth studies into their mechanisms of action have been carried out in vitro using doses which are unachievable in humans. In order to optimize the design of chemopreventive treatment, it is important to determine which of the many reported mechanisms of action are clinically relevant. In this review we consider the physiologically achievable doses for a few of the best studied agents (indole-3-carbinol, diindolylmethane, curcumin, epigallocatechin-3-gallate and resveratrol) and summarize the data derived from studies using these low concentrations in cell culture. We then cite examples of in vitro effects which have been observed in vivo. Finally, the ability of agent combinations to act synergistically or antagonistically is considered. We conclude that each of the compounds shows an encouraging range of activities in vitro at concentrations which are likely to be physiologically relevant. There are also many examples of in vivo studies which validate in vitro observations. An important consideration is that combinations of agents can result in significant activity at concentrations where any single agent is inactive. Thus, for each of the compounds reviewed here, in vitro studies have provided useful insights into their mechanisms of action in humans. However, data are lacking on the full range of activities at low doses in vitro and the benefits or otherwise of combinations in vivo.